A fast and reliable method for GHB quantitation in whole blood by GC–MS/MS (TQD) for forensic purposes - Castro, André Lobo (2015)
Gamma-Hydroxybutyric Acid (GHB) is an endogenous compound with a story of clinical use since the 1960’s. However, due to its secondary effects, it has become a controlled substance, entering the illicit market. A fully validated, sensitive and reproducible method for the quantification of GHB by methanolic precipitation and GC-MS/MS (TQD) in whole blood is presented. Using 100 µL of whole blood, obtained results included a LOD and LLOQ of 0.1 mg/L and a recovery of 86% in a working range between 0.1 and 100 mg/L. This method is sensitive and specific to detect the presence of GHB in small amounts of whole blood (both ante-mortem or post-mortem), and is, to the authors’ knowledge, the first GC-MS-MS TQD method that uses different precursor ions and product ions for the identification of GHB and GHB-D6 (internal standard). Hence, this method may be especially useful for the study of endogenous values in this biological sample.